Culture, Sustainability, and Communities: Exploring the Myths - Duxbury, Nancy; Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2010)
In the face of growing environmental and economic urgencies, issues of culture and sustainability are moving to the forefront of planning, policy, and programs in cities and communities of all sizes. This paper aims to advance this area of research by mapping the terrain of this emerging, disparate field within policy/planning contexts internationally. We examine the literature through three lenses: temporal, spatial and conceptual, which reveals rather weak linkages between the conceptual underpinnings of culture and sustainability and community planning praxis.
Keywords: Culture; Sustainability; Cities; Communities